Vertical Fiscal Imbalances and the Accumulation of Government Debt - Aldasoro, Inaki (IMF Working Papers; Working Paper, 2014)
Delegating fiscal decision making power to sub-national governments has been an area of interest for both academics and policymakers given the expectation that it may lead to better and more efficient provision of public goods and services. Decentralization has, however, often occurred on the expenditure and less on the revenue side, creating 'vertical fiscal imbalances' where sub-national governments' expenditures are not financed through their own revenues. The mismatch between own revenues and expenditures may have consequences for public finance performance. This study constructs a large sample of general and subnational level fiscal data beginning in 1980 from the IMF's Government Finance Statistics Yearbook. Extending the literature to the balance sheet approach, this paper examines the effects of vertical fiscal imbalances on government debt. The results indicate that vertical fiscal imbalances are relevant in explaining government debt accumulation suggesting a degree of caution when promoting fiscal decentralization. This paper also underlines the role of data covering the general government and its subectors for comprehensive analysis of fiscal performance.